Novel PCSK9 (Proprotein Convertase Subtilisin Kexin Type 9) Variants in Patients With Familial Hypercholesterolemia From Cape Town. Issue 2 (February 2021) - Huijgen, Roeland; Blom, Dirk J.; Hartgers, Merel L.; Chemello, Kévin; Benito-Vicente, Asier; Uribe, Kepa B.; Behardien, Zorena; Blackhurst, Dee M.; Brice, Brigitte C.; Defesche, Joep C.; de Jong, Annemiek G.; Jooste, Rosemary J.; et al.
Abstract : Objective: Familial hypercholesterolemia (FH) is characterized by elevated low-density lipoprotein-cholesterol and markedly increased cardiovascular risk. In patients with a genetic diagnosis, low-density lipoprotein receptor ( LDLR ) mutations account for >90% of cases, apolipoprotein B ( APOB ) mutations for ≈5% of cases, while proprotein convertase subtilisin kexin type 9 ( PCSK9 ) gain of function mutations are rare (<1% of cases). We aimed to evaluate the functional impact of several novel PCSK9 variants in a cohort of patients with FH by genetic cascade screening and in vitro functionality assays. Approach and Results: Patients with clinically diagnosed FH underwent genetic analysis of LDLR, and if negative, sequential testing of APOB and PCSK9 . We analyzed cosegregation of hypercholesterolemia with novel PCSK9 variants. Gain of function status was determined by in silico analyses and validated by in vitro functionality assays. Among 1055 persons with clinical FH, we identified nonsynonymous PCSK9 variants in 27 (2.6%) patients and 7 of these carried one of the 4 previously reported gain of function variants. In the remaining 20 patients with FH, we identified 7 novel PCSK9 variants. The G516V variant (c.1547G>T) was found in 5 index patients and cascade screening identified 15 additional carriers. Low-density lipoprotein-cholesterol levels were higher in these 15 carriers compared with the 27 noncarriers (236±73 versus 124±35 mg/dL; P <0.001). In vitro studies demonstrated the pathogenicity of the G516V variant. Conclusions: In our study, 1.14% of cases with clinical FH were clearly attributable to pathogenic variants in PCSK9 . Pathogenicity is established beyond doubt for the G516V variant. Abstract : Supplemental Digital Content is available in the text.